5(d+2)=3(d+-6)

Simple and best practice solution for 5(d+2)=3(d+-6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(d+2)=3(d+-6) equation:


Simplifying
5(d + 2) = 3(d + -6)

Reorder the terms:
5(2 + d) = 3(d + -6)
(2 * 5 + d * 5) = 3(d + -6)
(10 + 5d) = 3(d + -6)

Reorder the terms:
10 + 5d = 3(-6 + d)
10 + 5d = (-6 * 3 + d * 3)
10 + 5d = (-18 + 3d)

Solving
10 + 5d = -18 + 3d

Solving for variable 'd'.

Move all terms containing d to the left, all other terms to the right.

Add '-3d' to each side of the equation.
10 + 5d + -3d = -18 + 3d + -3d

Combine like terms: 5d + -3d = 2d
10 + 2d = -18 + 3d + -3d

Combine like terms: 3d + -3d = 0
10 + 2d = -18 + 0
10 + 2d = -18

Add '-10' to each side of the equation.
10 + -10 + 2d = -18 + -10

Combine like terms: 10 + -10 = 0
0 + 2d = -18 + -10
2d = -18 + -10

Combine like terms: -18 + -10 = -28
2d = -28

Divide each side by '2'.
d = -14

Simplifying
d = -14

See similar equations:

| 2/5w | | 14+2x+6=24 | | 1.25x-6=x | | 9a-2=-3 | | 48n^3=147 | | 5x-4(4y-5x)+6y= | | 40=w^2+13w | | P=(20+.05x)+.15(20+.05x) | | 3X-5=X+53 | | 5.8x+9=33.64+3x | | 48n^3-147=0 | | 2x^2-14-3x=0 | | 7-3x+8x=-13 | | 6+2InX=5 | | 3(x-2)+8=2(x-3) | | (Ft)(x)= | | ln(0.1)+2ln(x)-ln(2)=ln(5) | | 4/5*t=8 | | (32)x=38 | | 5x+10=30-5 | | 20x+7-4x=87 | | r-3/5=125/8 | | xsquare+4x=7x | | 9.8*a=20.58 | | 16-9v=2x-17 | | P^3-p^2-9p+9=0 | | 4x+8=2+10 | | X(x+9)=1 | | -x+6y=72 | | 8x+8y(-6y-3)=-24 | | g(-4)=(x+3)(x-2) | | 3(x-4)-3=15 |

Equations solver categories